Strategy to Increase Waqif Trust by Nazir Waqf Lazismu Trensains Sragen - Mulyono Jamal; Nurul Fathonah (ITB AAS INDONESIA Surakarta, 2022)
This research is to find out what strategies are carried out by an Islamic boarding school waqf institution to maintain and increase the trust of waqif. This research is qualitative research with a literature study approach, unstructured interviews, observation, analysis using a triangulation approach. The object of this research is Lazismu Trensains located in Muhammadiyah Pesantren Sains (Trensains) Sragen City, Central Java. This study found that several strategies were carried out by nazir waqf Lazismu Trensains to increase the trust of waqif, one of which was a transparent reporting system, intensely building active communication with donors and creating an online waqf platform, namely sedekahanaja.id which made it easier for waqifs to waqf. This study only explores the nazir strategy in Lazismu Trensains which is based on Islamic boarding school. There is no research that discusses the strategy of increasing waqif trust by nazir waqf in Muhammadiyah Islamic boarding school.